HIV pre‐exposure prophylaxis for adolescent girls and young women in Africa: from efficacy trials to delivery - Celum, Connie L; Delany‐Moretlwe, Sinead; Baeten, Jared M; Straten, Ariane; Hosek, Sybil; Bukusi, Elizabeth A; McConnell, Margaret; Barnabas, Ruanne V; Bekker, Linda‐Gail (Journal of the International AIDS Society, 2019)
Introduction Adolescent girls and young women (AGYW) in Africa have high HIV incidence despite scale‐up of HIV testing and HIV treatment. Placebo‐controlled trials of tenofovir‐based pre‐exposure prophylaxi (PrEP) in diverse populations demonstrated that PrEP works with close to 100% effectiveness if taken with high, but not perfect, adherence. Divergent efficacy estimates among African AGYW led to demonstration and implementation projects to better understand motivations for HIV prevention, uptake, adherence and persistence to PrEP. To inform PrEP programmes, the design and initial findings from PrEP demonstration projects for AGYW are reviewed. Discussion Early lessons from PrEP implementation projects among young African women include: (1) awareness and demand creation with positive messaging about the benefits of PrEP are critical to motivate AGYW to consider this novel prevention technology and to foster awareness among peers, partners, parents and guardians to support AGYW's effective PrEP use; (2) PrEP initiation is high in projects that are integrating PrEP into youth‐friendly clinics, family planning clinics and mobile clinics; (3) young African women at risk are initiating PrEP, based on behavioural characteristics, history of intimate partner violence, depression and 30% prevalence of chlamydia and/or gonorrhoea; (4) provision of youth‐friendly PrEP delivery programmes that integrate reproductive health services, including contraception and the diagnosis and treatment of sexually transmitted infections, increase health impact; (5) messages that emphasize the necessity for high adherence while at potential risk of HIV exposure and support strategies that addresses AGYW's adherence challenges are essential; and, (6) a substantial proportion of AGYW do not persist with PrEP, and strategies are needed to help AGYW assess their ongoing need, motivation and challenges with persisting with PrEP. Conclusions PrEP is feasible to implement in integrated reproductive health service delivery models to reach African AGYW. While PrEP demonstration projects indicate that women with behavioural risks and high rates of sexually transmitted diseases are initiating PrEP; effective strategies to support AGYW's adherence and persistence with PrEP are needed. Lessons learned from oral PrEP delivery, a novel first generation HIV prevention product, are relevant to longer‐acting and less adherence‐dependent strategies which are currently in clinical trials.